Introducing Indonesia and Opening Opportunities for Cooperation with Universities in Philippines - Erwin Kartinawati; Peni Pujiastuti; Yudi Wibowo; Sri Huning Anwariningsih; Andrik Purwasito (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
In the era of educational globalization, collaboration between universities across countries has become a strategic necessity to strengthen the exchange of knowledge, culture, and innovation. Indonesia, as a country with rich culture, languages, and significant academic potential, has the opportunity to expand its educational network with countries in Southeast Asia, including the Philippines. However, educational and cultural relations between Indonesia and the Philippines have not been optimally developed. In that regard, through this community service activity, a team of Indonesian academics seeks to comprehensively introduce Indonesia to the academic community in the Philippines, while also opening opportunities for collaboration between universities in education, research, and community service. This activity also represents the implementation of educational, language, and cultural diplomacy, demonstrating the contribution of Indonesian universities at the international level. This activity is expected to result in the signing and implementation of cooperation agreements